Development of betavoltaic cell technology production based on microchannel silicon and its electrical parameters evaluation. (March 2017) - Krasnov, A.A.; Starkov, V.V.; Legotin, S.A.; Rabinovich, O.I.; Didenko, S.I.; Murashev, V.N.; Cheverikin, V.V.; Yakimov, E.B.; Fedulova, N.A.; Rogozev, B.I.; Laryushkin, A.S.
Abstract: In the paper a manufacturing process of three-dimensional (3D) microchannel structure by silicon (Si) anodic etching was discussed. The possibility of microchannels formation allows to increase the active area more than 100 times. In this structure the p-n junction on the whole Si surface was formed. The obtained data allowed to evaluate the characteristics of the betavoltaic converter with a 3D structure by using isotope 63Ni with a specific activity of 10 Ci/g. Highlights: The microchannels formation possibility increases the active area more than 100 times. p-n junction on Si surface was formed.